CXCL2/CXCR2 axis induces cancer stem cell characteristics in CPT‐11‐resistant LoVo colon cancer cells via Gαi‐2 and Gαq/11. Issue 7 (14th December 2018) - Chen, Ming‐Cheng; Baskaran, Rathinasamy; Lee, Nien‐Hung; Hsu, Hsi‐Hsien; Ho, Tsung‐Jung; Tu, Chuan‐Chou; Lin, Yueh‐Min; Viswanadha, Vijaya Padma; Kuo, Wei‐Wen; Huang, Chih‐Yang
Abstract: Cancer stem cells (CSCs) exist in colon cancer and exhibit characteristics of stem cells which are due to lineages of tissues where they arise. Epithelial to mesenchymal transition (EMT)‐undergoing cancer cells display CSC properties and therapeutic resistance. Cancer and stromal cells comprise of a tumor microenvironment. One way the two populations communicate with each other is to secret CXC ligands (CXCLs). CXCLs are capable of causing chemotaxis of specific types of stromal cells and control angiogenesis. Double immunofluorescence, western blot analysis, and colony‐formation assay were carried out to compare parental and CPT‐11‐resistant LoVo cells. CPT‐11‐R LoVo colon cancer cells showed increased expression of CXCL1, CXCL2, CXCL3, and CXCL8. They displayed significantly increased intracellular protein levels of CXCL2 and CXCR2. CPT‐11‐R LoVo cells showed significantly elevated expression in aldehyde dehydrogenase 1 (ALDH1), cluster of differentiation 24 (CD24), cluster of differentiation 44 (CD44), and epithelial cell adhesion molecule (EpCAM). CXCL2 knockdown by short hairpin RNA resulted in reduced expression of CSC proteins, cyclins, EMT markers, G proteins, and matrix metalloproteinases (MMPs). Finally, Gαi‐2 was found to promote expression of CSC genes and tumorigenesis which were more apparent in the resistant cells. In addition, Gαq/11 showed a similar pattern with exceptions of EpCAM and MMP9. Therefore, CXCL2–CXCR2 axis mediates through Gαi‐2 and Gαq/11 to promote tumorigenesis and contributes to CSC properties of CPT‐11‐R LoVo cells. Abstract : Gαi‐2 was found to promote expression of cancer stem cell (CSC) genes and tumorigenesis which were more apparent in the resistant cells. In addition, Gαq/11 showed a similar pattern with exceptions of epithelial cell adhesion molecule (EpCAM) and matrix metalloproteinase 9 (MMP9). Therefore, CXCL2–CXCR2 axis mediates through Gαi‐2 and Gαq/11 to promote tumorigenesis and contributes to CSC properties of CPT‐11‐R LoVo cells.